2007
DOI: 10.1128/jvi.00281-07
|View full text |Cite
|
Sign up to set email alerts
|

Virus Subtype-Specific Features of Natural Simian Immunodeficiency Virus SIV smm Infection in Sooty Mangabeys

Abstract: Simian immunodeficiency virus (SIV) SIV smm naturally infects sooty mangabeys (SMs؉ T-cell depletion is unlikely to simply reflect higher levels of virus-mediated direct killing of CD4 ؉ T-cells. Taken together, this systematic analysis of the subtype-specific features of SIV smm infection in natural SM hosts identifies subtype-specific differences in the pathogenicity of SIV smm infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 65 publications
2
45
1
Order By: Relevance
“…Acquisition of CXCR4-mediated tropism for naïve CD4 ϩ T cells is strongly linked to accelerated CD4 ϩ T cell loss in HIVinfected humans, so it is uncertain whether the additional coreceptors used by these CXCR4-tropic SIVsmm Envs contribute further to disrupted CD4 ϩ T cell homeostasis. In contrast, we did not see distinct alternative coreceptor use or smCXCR4-mediated entry by isolates derived from SM naturally infected with subtype 5 SIVsmm isolates, which display more moderate levels of CD4 ϩ T cell loss (1). Thus, CD4 ϩ T cell loss in subtype 5 SIVsmm-infected SM is likely due to factors other than expanded tropism by the virus, at least for the coreceptors tested here.…”
Section: Discussioncontrasting
confidence: 46%
“…Acquisition of CXCR4-mediated tropism for naïve CD4 ϩ T cells is strongly linked to accelerated CD4 ϩ T cell loss in HIVinfected humans, so it is uncertain whether the additional coreceptors used by these CXCR4-tropic SIVsmm Envs contribute further to disrupted CD4 ϩ T cell homeostasis. In contrast, we did not see distinct alternative coreceptor use or smCXCR4-mediated entry by isolates derived from SM naturally infected with subtype 5 SIVsmm isolates, which display more moderate levels of CD4 ϩ T cell loss (1). Thus, CD4 ϩ T cell loss in subtype 5 SIVsmm-infected SM is likely due to factors other than expanded tropism by the virus, at least for the coreceptors tested here.…”
Section: Discussioncontrasting
confidence: 46%
“…An important common feature of SIV infection in natural hosts is that these animals consistently show levels of immune activation that are significantly lower than those observed in HIV-infected humans or SIV-infected RMs (13,14,(16)(17)(18)(19)(20)(32)(33)(34). In SMs, perhaps the most well-characterized model of natural SIV hosts, it was shown that chronic SIV infection is associated with (a) low levels of CD4 + and CD8 + T cell activation and proliferation in both peripheral blood and lymph nodes (14,(16)(17)(18); (b) no signs of increased levels of T cell apoptosis either in vivo or in vitro (17,(35)(36); (c) absence of the cell-cycle dysregulation associated with pathogenic HIV/SIV infections (37-39); and (d) preserved function of the T cell regenerative compartment, i.e., bone marrow, thymus, and lymph nodes (17,40).…”
Section: Natural Siv Infections Are Characterized By Low Immune Activmentioning
confidence: 99%
“…Figure 1 summarizes the key differences and similarities between nonpathogenic SIV infection of natural hosts and LTNPs. In a recent survey of 110 naturally SIV-infected SMs housed at the Yerkes National Primate Research Center, we found a mean viral load of 170,000 ± 205,000 copies/ml of plasma and a mean CD4 + T cell count of 1,067 ± 589 cells/mm 3 (19,20). This typical phenotype of natural SIV hosts - high CD4 + T cell counts despite high viral loads - is very different from the observation that in both HIV-infected individuals and experimentally SIVmac-infected RMs, high levels of virus replication predict faster disease progression (21)(22)(23).…”
Section: Basic Features Of Natural Siv Infectionmentioning
confidence: 99%
“…It has been noted that the genetic diversity of naturally circulating SIVsmm strains is roughly comparable to the diversity of the HIV-1 M group (1), and the predictive utility of SIV heterologous-challenge models rests in part on this observation. However, SIVsmm in sooty mangabeys represents a far more ancient lineage than HIV-1 in humans: the global diversity of the current HIV-1 epidemic harks back to a common ancestor about a century ago (43,89), while SIVsmm origins in sooty mangabey go back many millennia (90).…”
mentioning
confidence: 99%